Pengaplikasian Model Pengajaran dan Pembelajaran Secara Kontektual pada Mata Pelajaran IPS - Abdur Rozzaq; Agus Jatmiko; Adi Suranto (MODELING: Jurnal Program Studi PGMI, 2021)
In learning activities, there are various kinds of main variables that are interconnected, including curriculum, educators / teachers, the learning process, students. Judging from this, the teacher is required to be able to use various kinds of learning examples so that students can carry out learning activities properly. This is because students are not only objects but also as subjects in teaching and learning activities. Students must be prepared from the start to be able to interact with their environment, so that various types of learning methods can be used by the educator. One example of innovative learning is an example of a contextual teaching and learning model. The contextual teaching and learning model is a perception that supports educators to link teaching material modules using a concrete global context & encourages students to create interactions between insights & their application into their activities. In essence, an understanding of the Teaching Method of Basic Conception of Social Sciences which is imaginative, constantly innovates, and also requires evaluation. Student learning assessment is a factor that needs to be considered in order to determine the achievement of indicators and learning objectives, especially the evaluation of the cognitive domain, which requires students to understand, know, apply, analyze, synthesize. Constraints in the learning process, students only know & understand, but students cannot describe the material in detail.